Nouvelles données sur les caractéristiques morphologiques immatures du crâne chez les Homo erectus asiatiques - Antoine Balzeau (Bulletins et Mémoires de la Société d’Anthropologie de Paris)
It is critical to be able to recognize the juvenile specimens within the fossil record in order to determine the adult variability of the different taxa and to approach their ontogenetic and phylogenetic characteristics. Nevertheless, with regard to the Asian fossils assigned to Homo erectus, few cranial remains of juvenile individuals have been unearthed. Furthermore, these individuals are spread over a large chronological duration. Our purpose is to test the validity of the features generally used to estimate the developmental age of these fossils and to convey new information about the juvenile features of the cephalic skeleton in the species Homo erectus. Our results illustrate that growth standards defined for modern humans are not suitable to study the growth and development in Homo erectus. Moreover, the criteria frequently used to determine the development stage in Homo erectus would be barely meaningful. We show that the internal components of the cranial vault would differentiate at an early developmental age, as shown by the Mojokerto child. Similarly, cranial vault thickness would come within the adult range of variation early during growth, as shown for the frontal squama by Ngandong 2. The thickness of the frontal superstructures and of the occipital torus would increase later, but before the adult stage. This modification concerns all the internal components of the bone and principally the diploic layer. Moreover, our results suggest that the growth and development of the Homo erectus brain were different from those of modern humans. The transition from the endocranial shape of Mojokerto to the adult morphology for Homo erectus corresponds to a relative development of the frontal lobes, associated with an antero-posterior extension of the cerebral structures. Finally, the globularity of the brain and of the skull would persist late during the ontogenetic history in Homo erectus. The disappearance of these features would be due to an antero-posterior relative elongation of the endocast and of the cranial vault, as well as anterior enlargement of the frontal superstructures and posterior enlargement of the occipital superstructures.